ANALISIS PENGAKUAN ASET TETAP PADA PT. X - Rindu Reza Budiarti; Rida Perwita Sari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
. This article discusses the results of an independent internship program in the Merdeka Belajar Kampus Merdeka (MBKM) initiative conducted at PT X, with a focus on analyzing the recognition of fixed assets by PT X. This research uses a qualitative analysis approach with second-order data from PT X's 2023 financial statements and related notes. Understanding accounting policies, document verification, physical inspection of assets, and analysis of management estimates are part of the audit process. The main conclusion showed that there were errors in the recognition of fixed assets, especially when calculating the acquisition price, which did not include VAT of Rp 5,000,000. By revising the fixed asset recognition journal, the acquisition cost of the building was increased to Rp 250,000,000. The end result shows that, in accordance with accounting standards, PT X's financial statements now accurately reflect the value of its fixed assets. Suggestions include improved documentation, collaboration between departments, and tax compliance. This experience emphasizes the importance of accuracy in calculating the acquisition cost of fixed assets and coordination between departments to ensure financial reporting accuracy. This research provides valuable insight into real-world accounting and auditing practices, as well as the importance of compliance with accounting standards in maintaining the integrity of a company's financial statements.